Regional war, global consequences: Mounting damages to Ukraine’s agriculture and growing challenges for global food security - Martyshev, Pavlo; Nivievskyi, Oleg; Bogonos, Mariia (International Food Policy Research Institute, 2023)
Russia’s all-out war on Ukraine has inflicted devastating impacts that continue to mount more than a year after the invasion. As of September 2022, even before Russia’s winter bombing campaign, the total damage to Ukraine’s infrastructure was an estimated US$127 billion, equal to 64% of the country’s 2021 GDP. More than 14 million Ukrainians have left their homes, including more than 8 million refugees. These impacts have global economic effects as well — particularly on agricultural markets and food security. Damage to Ukrainian agriculture and production losses also continue to mount. This has created severe economic uncertainty, driving many Ukrainian farmers to the brink of bankruptcy and substantially depressing agricultural output — contributing to high prices and price volatility around the world. In this post, we outline the war’s impacts on Ukrainian production and exports of key crops and their continuing global reverberations.